2015
DOI: 10.18178/ijke.2015.1.3.035
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Influence Organizational Culture toward Intellectual Capital

Abstract: Abstract-Organizational culture commonly referred as work culture and is important in the SME (small and medium enterprises). If the organizational culture that is used in the SME is right and good then SME will go well. One of the assets owned by an SME is intellectual capital and it is an intangible asset that also plays an important role in an SME. This study wants to analyze the influence of organizational culture on the intellectual capital.This study conducted by case study on Bina Karya SME that is loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(3 reference statements)
1
1
0
Order By: Relevance
“…In addition, the established organizational culture could support the employees as well in producing an optimal intellectual performance and building a harmonious relationship with the company's business partners. This research finding was consistent with the research conducted by Rumanti et al (2015) who found that organizational culture had a positive significant influence on intellectual capital and could drive the company's intellectual capital better.…”
Section: Assessing the Inner Model Or Structural Modelsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the established organizational culture could support the employees as well in producing an optimal intellectual performance and building a harmonious relationship with the company's business partners. This research finding was consistent with the research conducted by Rumanti et al (2015) who found that organizational culture had a positive significant influence on intellectual capital and could drive the company's intellectual capital better.…”
Section: Assessing the Inner Model Or Structural Modelsupporting
confidence: 91%
“…When an organization member knows a positive organizational culture, then the work environment is more likely to be more fun and hence boosts the spirit to work (Sadri et al, 2001). One of the previous studies on organizational culture is conducted by Rumanti, Hidayat, and Yordy (2015) who investigate the influence of organizational culture on intellectual capital and the finding is that good organizational culture and support at work will improve the intellectual capital which consists of human capital, structural capital, and relational capital. Meanwhile, the research conducted by Astuti (2011) shows that organizational culture does not have a significant influence on human capital, customer capital, and structural capital.…”
Section: Introductionmentioning
confidence: 99%